Actor-based identification of deforestation drivers paves the road to effective REDD+ in DR Congo. (15th December 2016) - Moonen, Pieter C.J.; Verbist, Bruno; Schaepherders, Jarrik; Bwama Meyi, Marcel; Van Rompaey, Anton; Muys, Bart
Highlights: We executed the first cross-scale study of drivers and actors of deforestation in DR Congo. Significant variation in deforestation was detected across villages and households. Main deforesters are not subsistence but market-oriented, asset-rich farmers. Villages differ in deforestation rates and social-ecological conditions requiring spatial targeting of policy interventions. Limiting driver studies to the national level does not suffice to design effective REDD+ policies. Abstract: Conversion of tropical forests remains high on the international agenda, but the effectiveness of the proposed framework to reduce emissions from deforestation and degradation (REDD+) has been questioned. We hypothesized that an effective implementation of REDD+ would require understanding of the functioning of the local social-ecological system and modulation of actions to the actors' characteristics and motivations in the affected areas. But cross-scale studies of deforestation drivers are seldom performed, given the difficulties to obtain consistent datasets, particularly for the local scale. We addressed this issue for the agricultural expansion in the Central Basin of the Democratic Republic of Congo, a REDD+ priority country. We detected considerable variation in deforestation rate within scale levels, with highest variation at village and household level, which had gone unnoticed so far. Population density and market access are the main sources of inter- village variation, although cultural factors affect magnitude by an order of 2. Individual household contributions to deforestation are strongly unevenly distributed, with longer established households and better market integrated households deforesting more than others. Our results reveal that due to the current lack of cross-scale studies, policy makers are lacking context specific relevant information at local scale needed to design efficient, effective and equitable policies. They also challenge the dominant discourse that agricultural expansion in the Basin is driven by poor subsistence farmers, and make us add actor-oriented interventions and land use zoning as two crucial requirements for REDD+ intensification policies to become effective.